High-resolution genotyping of the endemic Salmonella Typhi population during a Vi (typhoid) vaccination trial in Kolkata. - Kathryn E Holt; Shanta Dutta; Byomkesh Manna; Sujit K Bhattacharya; Barnali Bhaduri; Derek J Pickard; R Leon Ochiai; Mohammad Ali; John D Clemens; Gordon Dougan (Public Library of Science (PLoS), 2012)
Typhoid fever, caused by Salmonella enterica serovar Typhi (S. Typhi), is a major health problem especially in developing countries. Vaccines against typhoid are commonly used by travelers but less so by residents of endemic areas.We used single nucleotide polymorphism (SNP) typing to investigate the population structure of 372 S. Typhi isolated during a typhoid disease burden study and Vi vaccine trial in Kolkata, India. Approximately sixty thousand people were enrolled for fever surveillance for 19 months prior to, and 24 months following, Vi vaccination of one third of the study population (May 2003-December 2006, vaccinations given December 2004).A diverse S. Typhi population was detected, including 21 haplotypes. The most common were of the H58 haplogroup (69%), which included all multidrug resistant isolates (defined as resistance to chloramphenicol, ampicillin and co-trimoxazole). Quinolone resistance was particularly high among H58-G isolates (97% Nalidixic acid resistant, 30% with reduced susceptibility to ciprofloxacin). Multiple typhoid fever episodes were detected in 22 households, however household clustering was not associated with specific S. Typhi haplotypes.Typhoid fever in Kolkata is caused by a diverse population of S. Typhi, however H58 haplotypes dominate and are associated with multidrug and quinolone resistance. Vi vaccination did not obviously impact on the haplotype population structure of the S. Typhi circulating during the study period.